STRIDER (Sildenafil TheRapy in dismal prognosis early onset fetal growth restriction): an international consortium of randomised placebo-controlled trials - A. Pels; L. C. Kenny; Z. Alfirevic; P. N. Baker; Peter von Dadelszen; C. Gluud; C. T. Kariya; B. W. Mol; A. T. Papageorghiou; A. G. van Wassenaer-Leemhuis; W. Ganzevoort; K. M. Groom; et al. (BMC, 2017)
Abstract Background Severe, early-onset fetal growth restriction due to placental insufficiency is associated with a high risk of perinatal mortality and morbidity with long-lasting sequelae. Placental insufficiency is the result of abnormal formation and function of the placenta with inadequate remodelling of the maternal spiral arteries. There is currently no effective therapy available. Some evidence suggests sildenafil citrate may improve uteroplacental blood flow, fetal growth, and meaningful infant outcomes. The objective of the Sildenafil TheRapy In Dismal prognosis Early onset fetal growth Restriction (STRIDER) collaboration is to evaluate the effectiveness of sildenafil versus placebo in achieving healthy perinatal survival through the conduct of randomised clinical trials and systematic review including individual patient data meta-analysis. Methods Five national/bi-national multicentre randomised placebo-controlled trials have been launched. Women with a singleton pregnancy between 18 and 30 weeks with severe fetal growth restriction of likely placental origin, and where the likelihood of perinatal death/severe morbidity is estimated to be significant are included. Participants will receive either sildenafil 25 mg or matching placebo tablets orally three times daily from recruitment to 32 weeks gestation. Discussion The STRIDER trials were conceived and designed through international collaboration. Although the individual trials have different primary outcomes for reasons of sample size and feasibility, all trials will collect a standard set of outcomes including survival without severe neonatal morbidity at time of hospital discharge. This is a summary of all the STRIDER trial protocols and provides an example of a prospectively planned international clinical research collaboration. All five individual trials will contribute to a pre-planned systematic review of the topic including individual patient data meta-analysis. Trial registrations New Zealand and Australia: ACTRN12612000584831 . Registered 30/05/2012. Canada: NCT02442492 . Registered 05/05/2015. Ireland: CT 900/572/1 . Registered 15/07/2015. The Netherlands: NCT02277132 . Registered 29/09/2014. United Kingdom: ISRCTN39133303 . Registered 31/07/2014.